Економічна сутність і значення інвестицій та інвестиційної діяльності суб’єктів господарювання - Гвоздєв, Ю. В.; Гвоздев, Ю. В.; Gvozdev, Yu. (ЦНТУ, 2018)
В статті розкривається економічна сутність і значення інвестиційної діяльності суб’єктів господарювання. Узагальнюючи вищезазначене, систематизуємо найбільш важливі ознаки інвестицій: дозволяють реалізувати безліч цілей – економічні (у вигляді отримання доходу), менеджменту (підвищення якості та конкурентоспроможності продукції, оптимізації витрат та ін.), неекономічні (соціальні, екологічні); сприяють перетворенню різних ресурсів господарюючих суб’єктів у альтернативні види активів; забезпечують відповідність ринковим законам попиту та пропозиції на інвестиційні ресурси та послуги; супроводжуються ризиками вкладення капіталу, тобто ймовірністю очікуваних результатів цілям інвестування; характеризуються невизначеністю термінів отримання досягнутого ефекту від здійснення інвестицій, а також залежністю термінів отримання вигод від управлінських рішень інвестора. В статье раскрывается экономическая сущность и значение инвестиционной деятельности субъектов хозяйствования. Обобщая вышесказанное, систематизируем наиболее важные признаки инвестиций: позволяют реализовать множество целей - экономические (в виде получения дохода), менеджмента (повышение качества и конкурентоспособности продукции, оптимизации затрат и др.), Неэкономические (социальные, экологические) способствуют превращению различных ресурсов хозяйствующих субъектов в альтернативные виды активов; обеспечивают соответствие рыночным законам спроса и предложения на инвестиционные ресурсы и услуги; сопровождаются рисками вложения капитала, то есть вероятностью ожидаемых результатов целям инвестирования; характеризуются неопределенностью сроков получения достигнутого эффекта от осуществления инвестиций, а также зависимостью сроков получения выгод от управленческих решений инвестора. The purpose of the study is to develop theoretical and methodological provisions for assessing the content of the concept of "investment activity" of business entities. The study of the foreign and domestic theory of investment activity, the theoretical analysis of the methods of state regulation of the investment process made it possible to determine the range of issues relating to the instruments of the investment mechanism. They can be summarized as follows: means of knowledge and economic categories (as an instrument for understanding the functioning of the investment mechanism and the financial regulation of the activities of investment institutes, as well as the results and means of this knowledge) used in the theory and practice of studying the problems of improving the investment mechanism; institutes that carry out state financial regulation concerning the subjects of investment activity; principles and rules, functions, tasks and types of their production activities; methods and levers of the investment mechanism that are used in the process of state (administrative) and market (economic) regulation of the activity of investment institutes. The category as a broad concept reflects the most general and important properties, signs, connections and relations of objects, phenomena, processes, etc. Summarizing the above, we systematize the most important signs of investment: they can realize many goals - economic (in the form of income generation), management (improving the quality and competitiveness of products, optimizing costs, etc.), non-economic (social, environmental); contribute to the transformation of various resources of economic entities into alternative types of assets; ensure compliance with market laws of demand and supply for investment resources and services; accompanied by risks of capital investment, that is, the probability of expected results for investment purposes; are characterized by uncertainty of the timing of obtaining the achieved effect from the investment, as well as the dependence of the timing of obtaining benefits from the managerial decisions of the investor. On the basis of the listed properties of investments it can be noted that this is a purposeful investment of capital that is not connected with current consumption and involves the transformation of resources of economic entities from one form to another in order to generate profit, as well as to achieve another economic and non-economic long-term effect.
Экономическая сущность и значение инвестиций и инвестиционной деятельности субъектов хозяйствования
Economic Essence and Value of Investments and Investment Activity of Business Entities
Keywords: інвестиція; капітальні вкладення; суб’єкт господарювання; діяльність; фінансові ресурси; инвестиция; капитальные вложения; субъект хозяйствования; деятельность; финансовые ресурсы; investment; capital investments; business entity; activity; financial resources